SOSIALISASI ARTI PENTING DAN STRATEGI PENGUATAN MEREK KOPI LOKAL “GUNUNG CIREMAI” UNTUK MENINGKATKAN OMSET PENJUALAN - Wachdijono, Wachdijono; Jaeroni, Akhmad (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2021)
ABSTRACTIn fact, it shows that finding local brand coffee drinks is more difficult than non-local brands. This is related to the position of the product brand in the market. If the position is very strong, the products will still exist and be easily found everywhere. This Community Service activity aims to disseminate the importance of the brand and strategies / efforts to strengthen the local coffee product brand "Gunung Ciremai" in Cibeureum Village, Cilimus District, Kuningan Regency. The implementation methods are socialization, discussion and pre-test post-test. The result was that there was an increase in the knowledge and understanding of local brand coffee business actors on the importance of brands and brand strengthening strategies so that they could become a strategic basis for the implementation of brand strengthening that has been carried out so far. The partners play a role as the target for the implementation of service activities so that cooperation is needed between the Gunung Jati University Community Service Institute and partners.